Pengaruh Integritas Dan Kompetensi Terhadap Kinerja Pegawai (Studi Pada Kantor Wilayah Direktorat Jenderal Bea Dan Cukai Sumatera Bagian Timur) - Putri Anggraini; Dewi Purnamasari, Endah; Emilda (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study aims to determine and analyze the influence of integrity and competence on employee performance at the Regional Office of the Directorate General of Customs and Excise (DJBC) of Eastern Sumatra. The research was conducted based on the reality that employee performance in public institutions often fluctuates, which may be influenced by differences in employees’ ethical attitudes and skill levels. The quality of human resources in public organizations is determined not only by technical capability but also by the moral integrity of each employee. This research uses a quantitative approach with a saturated sampling technique, in which all 80 employees at the Regional Office of DJBC Eastern Sumatra were used as respondents. Data were collected using a questionnaire and analyzed through multiple linear regression to examine the effect of the independent variables (integrity and competence) on the dependent variable (employee performance).The results show that both integrity and competence have a positive and significant effect on employee performance, either partially or simultaneously. The t-test results show that integrity significantly influences performance (t = 1.971 > t-table = 1.664), while competence also significantly affects performance (t = 9.062 > t-table = 1.664). The F-test result (F = 239.120 > F-table = 3.12) shows that both variables simultaneously influence employee performance, with an R² value of 0.928. This indicates that 92.8% of the variation in performance can be explained by integrity and competence, while the remaining 7.2% is influenced by other factors not examined in this study.